2011
DOI: 10.1111/j.1530-0277.2011.01668.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Traits Predicting Alcohol Drinking in Outbred Rats: An Investigation of Anxiety, Novelty Seeking, and Cognitive Flexibility

Abstract: These findings confirm that preexisting anxiety-related behavior predicts alcohol intake under several schedules of alcohol access. Moreover, when access is unlimited, the high-anxiety-related group exhibited an increase in bout size, but not frequency, of drinking. In addition, we show that modest intake when alcohol is restricted may or may not progress to excessive intake when the drug is freely available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 52 publications
2
26
2
Order By: Relevance
“…This finding is in line with previous studies showing the association of anxiety-like behavior and high alcohol consumption (e.g. [10,12]) but contrasts our recent finding of risk-assessment behavior being associated with high voluntary alcohol intake [16] indicating on the complexity in assessing behavioral predispositions to alcohol intake as well as alcohol-induced effects on behavior. However, these results demonstrate that even if differences cannot be seen between the alcohol-and water-drinking groups, there are individual differences among the alcohol-drinking animals that become evident when studying subgroups of animals in more detail.…”
Section: Behavior In Low-drinking and High-drinking Animalscontrasting
confidence: 48%
“…This finding is in line with previous studies showing the association of anxiety-like behavior and high alcohol consumption (e.g. [10,12]) but contrasts our recent finding of risk-assessment behavior being associated with high voluntary alcohol intake [16] indicating on the complexity in assessing behavioral predispositions to alcohol intake as well as alcohol-induced effects on behavior. However, these results demonstrate that even if differences cannot be seen between the alcohol-and water-drinking groups, there are individual differences among the alcohol-drinking animals that become evident when studying subgroups of animals in more detail.…”
Section: Behavior In Low-drinking and High-drinking Animalscontrasting
confidence: 48%
“…In fact, we have shown that when screened for their innate anxiety-like behavior, high-anxious mice displayed greater consumption and preference for ethanol but not for saccharin and quinine suggesting alterations in the rewarding effects of alcohol [40]. Also, in rats, preexisting anxiety-related behavior predicts alcohol intake under several schedules of alcohol access [68]. In addition, when animals were separated into anxious and non-anxious groups based on their performance in the EPM test, it has been shown that rats that were initially classified as anxious showed a significantly higher intake and preference for ethanol during the initiation phase of the voluntary drinking procedure than non-anxious animals [69].…”
Section: Discussionmentioning
confidence: 93%
“…A possible explanation for the day 2 withdrawal-induced preference for light is that ethanol is an appetitive stimulus for many animals, including zebrafish [24], [42], [43]. Additionally, rodents exposed to ethanol have been shown to search actively for ethanol and consume it freely if it is found [44], [45]. This may be due, in part, to an increase in glutamatergic neurotransmission that increases alcohol craving [3].…”
Section: Discussionmentioning
confidence: 99%